2022
DOI: 10.3390/su14138153
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Polish Consumers in Relation to Meals Ordered in Food Service Establishments in the Context of Plate Waste

Abstract: In the food service industry, food is wasted at every stage of the process. A significant part of food wastage is the so-called plate waste, i.e., food left by the consumer on the plate. The purpose of this research was to analyze the behavior of Polish consumers in relation to meals ordered in food establishments. The following issues were taken into account: leaving an unfinished meal on a plate and reasons for it, taking an unfinished meal home, and ordering half portions. The study was conducted on a repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
(68 reference statements)
1
3
0
Order By: Relevance
“…The indicated reasons for throwing away were preparing too large a portion or a distasteful dish. The results of the research related to the structure of wasted food products are comparable with the results of surveys conducted by other authors in different countries, e.g., Czech Republic [63], Canada [64], Germany [65], Morocco [66], Poland [7,40,41], Hungary [67], Italy [23,65,68], Saudi Arabia [69] and multi-level analysis [70]. Regarding the research conducted in Poland on the types of discarded products, Tomaszewska et al [41] showed that the most frequently discarded products were vegetables and meat.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The indicated reasons for throwing away were preparing too large a portion or a distasteful dish. The results of the research related to the structure of wasted food products are comparable with the results of surveys conducted by other authors in different countries, e.g., Czech Republic [63], Canada [64], Germany [65], Morocco [66], Poland [7,40,41], Hungary [67], Italy [23,65,68], Saudi Arabia [69] and multi-level analysis [70]. Regarding the research conducted in Poland on the types of discarded products, Tomaszewska et al [41] showed that the most frequently discarded products were vegetables and meat.…”
Section: Discussionsupporting
confidence: 85%
“…According to Conrad et al, the causes of food waste are increasing due to a higher quality of living [38,39], stating that single-person households or young professionals often buy more than they need. Bilska et al [40] and Tomaszewska et al [41] found that more food was wasted often by young people in Poland, both in households and in meals ordered in food establishments. The authors showed that people with a university-level education wasted food more often.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is difficult for young people to estimate how much produce they need in their homes and how much food needs to be cooked [ 87 , 88 ]. However, leaving plate leftovers at eating establishments also contributes to food waste [ 89 ]. Lack of food and nutrition knowledge and cooking experience was also a reason [ 87 , 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes consumers are guided by fashion when choosing a product, especially in the case of products labeled "light", "lekki", "fit" or "fitness". Sometimes the choice of food by consumers is accidental because not every consumer has sufficient knowledge about food [8,9,10,11,12]. The insufficiently regulated food market and the producers' desire to achieve high profits from the sale of products cause the situation that there are products on the Polish market that do not meet the standards.…”
Section: Introductionmentioning
confidence: 99%